Low temperature Solution-Processed ZnO film on flexible substrate. (1st June 2016) - Hong, JeongSoo; Wagata, Hajime; Katsumata, Ken-ichi; Matsushita, Nobuhiro
Abstract: Transparent conductive ZnO films were directly deposited on unseeded polyethersulfone (PES) substrates with a spin-spray method using aqueous solution at a low substrate temperature of 85 °C. All ZnO films were crystalline with wurtzite hexagonal structure and impurity phases were not detected. ZnO films deposited without citrate ions in the reaction solution had a rod array structure. In contrast, ZnO films deposited with citrate ions in the reaction solution had a continuous, dense structure. The transmittance of the ZnO films was improved from 11.9% to 85.3% as their structure changed from rod-like to continuous. After UV irradiation, the ZnO films with a continuous, dense structure had a low resistivity of 9.1×10 −3  Ω cm, high carrier concentration of 2.7×10 20  cm −3 and mobility of 2.5 cm 2  V −1  s −1 .